2017
DOI: 10.1137/15m1047076
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Transfer with Long-Range Interactions: Regularity and Asymptotics

Abstract: International audienceThis work is devoted to radiative transfer equations with long-range interactions. Such equations arise in the modeling of high frequency wave propagation in random media with long-range dependence. In the regime we consider, the singular collision operator modeling the interaction between the wave and the medium is conservative, and as a consequence wavenumbers take values on the unit sphere. Our goals are to investigate the regularizing effects of grazing collisions, the diffusion limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…The hypoelliptic property of the associated integro-differential operator was also analyzed. Similar results have been obtained in [17,18] for the radiative transfer equation with long-range interactions. Analyzing the limiting scaling of this equation, the authors demonstrated the emergence of a Fokker-Planck type operator in the highly forward-peaked limit, with a diffusion component consisting of another singular integral operator whose high frequency behavior equals that of the Laplace-Beltrami operator on the sphere.…”
supporting
confidence: 87%
“…The hypoelliptic property of the associated integro-differential operator was also analyzed. Similar results have been obtained in [17,18] for the radiative transfer equation with long-range interactions. Analyzing the limiting scaling of this equation, the authors demonstrated the emergence of a Fokker-Planck type operator in the highly forward-peaked limit, with a diffusion component consisting of another singular integral operator whose high frequency behavior equals that of the Laplace-Beltrami operator on the sphere.…”
supporting
confidence: 87%
“…When t t S := (−λ 1 ) −1 , the distribution of the angle is almost uniform and particles are in a diffusive regime. At such large times, the solution f (t, x, k) to the RTE (1) does not depend on k anymore and satisfies a diffusion equation [22] (see also [13] in the context of singular kernels). For these time scales, it is preferrable to solve a diffusion equation instead of the RTE, and we therefore consider times not significantly We represent in Figure 13 the characteristic time t S as a function of α for a(x) = a 0 = 0.1.…”
Section: Simulationsmentioning
confidence: 99%
“…Regarding the regularity of f , it was established in [13,14] that f is C ∞ in all variables for all t > 0, which is in stark contrast with the SR case. The regularity is reminiscent of the hypoelliptic nature of (1) when F is not integrable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RTE (1.1) has been studied in the whole domain using slightly different approaches, based on hypo-ellipticity techniques [6], in the references [1,21]. References treating problems with boundaries are scarce in the context of kinetic equations with singular scattering, however, for the classical kinetic Fokker-Planck equation with absorbing boundary we refer to [26,27].…”
Section: Preliminariesmentioning
confidence: 99%